Cross‐cultural adaptation and validation of the Arabic version of the foot function index in patients with chronic lateral ankle instability - Mohammed I. Amri; Msaad M. Alzhrani; Ahmad D. Alanazi; Mazen M. Alqahtani; Faizan Zaffar Kashoo (Journal of Foot and Ankle Research, 2022)
Abstract Background The English version of the Foot Function Index (FFI) is a reliable and valid tool for measuring pain and functional instability due to chronic lateral ankle instability (CLAI). However, its use among Arabic speakers with CLAI is limited because of the unavailability of the Arabic version of the FFI (FFI‐Arb). This study aimed to translate, cross‐culturally adapt and validate the FFI from the original English version into Arabic. Methods The FFI questionnaire was translated using the Beaton guidelines. Two‐hundred‐and‐thirty native Arabic‐speaking participants with CLAI were recruited from different physiotherapy clinics in Saudi Arabia. The convergent validity of the FFI‐Arb was tested using the Spearman correlation with the Arabic version Cumberland ankle instability tool (CAIT‐Arab). Test‐retest reliability was tested among 92 participants who completed the form again after seven days. Results Two‐hundred‐and‐thirty participants were enrolled (mean age = 32.09, Standard deviation (SD) = 8.64 years old). There was excellent internal consistency for the three subscales of FFI: pain (0.95), disability (0.97), and activity limitation (0.86), as for the total score (0.98). Convergent validity was analyzed by Spearman rank correlation between the new translated versions of FFI‐Arb and CAIT‐Arab. The total FFI‐Arb and CAIT‐Arab scores were moderately correlated (rho = − 0.569; p < 0.001). Subscales of FFI‐Arb, such as pain, disability, and activity limitation, were also moderately correlated with CAIT‐Arab (rho = − 0.565, rho = − 0.561, rho = − 0.512; p < 0.001). The construct validity was confirmed by principal component analysis (factor analysis) showing a three‐factor structure (eigenvalue 1) of FFI‐Arb with a total variance of 77.3%. Test‐retest reliability was excellent for the total score of the FFI‐Arb and all its subscales (interclass correlation coefficient = 0.984–0.999). Conclusions The FFI‐Arb is a reliable and valid tool for Arabic‐speaking patients with CLAI. The FFI‐Arb can be utilized in hospitals and clinics in Arabic speaking countries.